Chemosensory Gene Expression for Two Closely Relative Species Rhodnius robustus and R. prolixus (Hemiptera, Reduviidade, Triatominae) Vectors of Chagas Disease - Marchant, Axelle; Mougel, Florence; Jacquin-Joly, Emmanuelle; Almeida, Carlos E.; Blanchet, Denis; Bérenger, Jean-Michel; da Rosa, João A.; Harry, Myriam (Frontiers in Ecology and Evolution, 2021)
Rhodnius prolixus and R. robustus, are two closely related species, vectors of Trypanosoma cruzi, the causative agent of Chagas disease, but they clearly exhibit a clear-cut evidence in their ecological behavior. Rhodnius prolixus is considered as a domiciliated species while R. robustus only sporadically visits human houses in Amazonia. We performed a chemosensory gene expression study via RNA-seq for these two species and also included a laboratory introgressed R. robustus strain. We built an assembled transcriptome for each sample and for both sexes and compiled all of them in a reference transcriptome for a differential gene expression study. Because genes specifically expressed in one condition and not expressed in another may also reflect differences in the adaptation of organisms, a comparative study of the presence / absence of transcripts was also performed for the chemosensory transcripts, namely CSPs, OBPs, ORs, GRs and IRs, as well as Takeout (TO) transcripts because Takeout proteins have been proposed to be associated with chemosensory perception in both olfactory and taste system. In this study, twelve novel TO transcripts were annotated from R. prolixus genome. Among the 199 transcripts of interest annotated in this study 93% were conserved between R. prolixus and the sylvatic R. robustus. Moreover, 10 transcripts of interest were specifically expressed in one sex and absent in the other. Three chemosensory transcripts were found expressed only in reared R. prolixus (CSP19, OBP9, OR89) and only one in the sylvatic R. robustus (OR22). More generally, a large set of transcripts were found differentially expressed (DE) between males and females (1,630), with a majority of them (83%) over-expressed in males. Between environmental conditions 8,596 transcripts were DE, most of them (67%) were over-expressed in the sylvatic R. robustus samples, including 17 chemosensory transcripts (4 CSPs, 1 OBP, 5 ORs, 1 GR, 4 IR, 2 TO), but four of them (OBP19, OR13, OR40, OR79) were over-expressed in the reared samples.